Application Of Guided Imagination In Hypertension Management Among Hypertension Adults And Adult Families In Depok City - Rianty, Dian Asih; Sahar, Junaiti; Widyatuti, Widyatuti (Fakultas Kedokteran, 2022)
Hypertension is a non-communicable disease with an increasing prevalence every year and is one of the causes of death due to complications that occur in adulthood. Stress management is a part of hypertension management. The purpose of this study is to provide an overview of the implementation of evidence-based interventions (evidence based practice) guided imagination interventions in family nursing care to reduce blood pressure and stress perception in adults and adult families. The method used is a case study method with a fact-based nursing practice approach in 10 adult families with hypertension problems in Depok City. The measuring instrument used to measure the perception of stress is the Perceived Stress Scale (PSS). The results showed an increase in family knowledge, attitudes and skill in caring for hypertensive adults with values of 30.3%, 34,25% and 33%. The decrease in TDS from 156±15,05 to 148 ±13,16 and TDD from 101±11,00 to 95±9,78 and the average stress perception from 5,0 to 2.4. The guided imagery nursing intervention had an effect on decreasing blood pressure (p value < 0.05) and stress perception (p value < 0.05) Guided imagery intervention can be an effective intervention option in managing the health of family members with hypertension.